SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BAHAN BAKU PRODUKSI DENGAN METODE WEIGHTED PRODUCT PADA PT. LUHAI INDUSTRI - Irma Yunita Ruhiawati; Mochamad Yusuf Romdoni (Program Studi Sistem Informasi, Universitas Banten Jaya, 2020)
This study aims to be able to assist PT Luhai Industri Indonesia in processing data of new raw materials by making appropriate decisions with prices that are quite economical but with good enough quality, while the data processing techniques here use the decision support system method to determine adequate raw material production good and efficient. So not only is the information needed faster, the time needed to process the data will be faster. In the process of building a decision support system for the selection of raw materials for production using a system development method with a weighted product that uses a multiplication formula to link the rating of each attribute, where the rating must be raised first with the weight of the attribute concerned, in this study will use a method approach Waterfall in the development of the system from collecting data for user needs to the data to be processed into an attribute and weighting with the weighted product method in determining decisions on the final result of the software to be made, while the tools used in research to describe the flow of the system this is by using a structured method namely UML (Unfield Method Language) in describing the functional program model. This decision support system software will be built with Visual Studio 2010 programming language with a client server system so to adjust the system here will use MySQl as the database.